Cardioprotection of mAb2G4/ODN/lip on Myocardial Ischemia-Reperfusion Injury via Inhibiting the NF-κB Signaling Pathway - Zujin Xu; Zhuoran Wei; Yali Zhu; Guoqing Jing; Liufang Chen; Jia Zhan; Yun Wu (Hindawi-Wiley, 2023)
Substantial evidence suggests that the interventions of NF-κB would likely effectively prevent inflammatory response and reduce myocardial damage in the ischemic myocardium. And the NF-кB decoy ODN is a specific inhibitor that suppresses the expression of NF-κB. Herein, we revealed the effect and possible mechanism of mAb2G4/ODN/lip on myocardial ischemia-reperfusion injury (MI/RI). As shown in the results, post-treatment with mAb2G4/ODN/lip improved the impaired histological morphology in the MI/RI model and elevated cell viability in the H/R model. The mAb2G4/ODN/lip complex inhibited the NLRP3 signaling pathway and decreased the expression of LDH, IL-1β, TNF-α, IL-6, and MDA. Mechanistically, we demonstrated that post-treatment with mAb2G4/ODN/lip exerted protective effects against I/R injuries by inhibiting the NF-кB-related inflammatory response. In summary, the present study may offer a novel therapeutic strategy for treating MI/RI.